PERANAN MAMAK/PAMAN TERHADAP KEMENAKAN DALAM ADAT PERKAWINAN MASYARAKAT KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Juswandi Juswandi; Akbarizan Akbarizan (Ensiklopedia of Journal, 2023)
The purpose of this research is to understand and analyze the role of mamak/uncle in marriage customs in Kuantan Hilir Seberang District, Kuantan Singingi Regency. The method used is descriptive qualitative method. interviews with traditional leaders and references to several books related to the research title. Being a mamak/uncle is very much needed by their nephews, especially in the marriage process. when his nephew wanted to marry a mamak who would prepare everything, especially making correspondence. As for the letter prepared by the mamak/uncle, the permit was then forwarded to the mamak balobe from the mamak balobe Barula to the mamak penghulu from the mamak penghulu to the village head. After the letter was signed, it was followed by a letter to the Office of Religious Affairs (KUA). If this process is neglected or violated, the marriage is null and void according to customary law.Keywords: The Role of Mamak/Uncle in Marriage Customs